Plane-Wave Ultrasound Beamforming Through Independent Component Analysis. (May 2021) - Goudarzi, Sobhan; Asif, Amir; Rivaz, Hassan
Highlights: We propose a new framework for adaptive plane-wave beamforming wherein apodization weights are estimated through independent component analysis (ICA). The proposed method reconstructs the whole image simultaneously. The proposed method simultaneously improves the resolution and contrast while the resulting image is also visually appealing. The proposed algorithm is strongly robust when some of channels are noisy. Abstract: Background and Objective : Beamforming in coherent plane-wave compounding (CPWC) is an essential step in maintaining high resolution, contrast and framerate. Adaptive methods have been designed to achieve this goal by estimating the apodization weights from echo traces acquired by several transducer elements. Methods : Herein, we formulate plane-wave beamforming as a blind source separation problem, where the output of each transducer element is considered as a non-independent observation of the field. As such, beamforming can be formulated as the estimation of an independent component out of the observations. We then adapt the independent component analysis (ICA) algorithm to solve this problem and reconstruct the final image. Results : The proposed method is evaluated on a set of simulations, real phantom, and in vivo data available from the plane-wave imaging challenge in medical ultrasound. Moreover, the results are compared with other well-known adaptive methods. Conclusions : Results demonstrate that the proposed method simultaneously improves the resolution and contrast.